The Nuts and Bolts of Designing and Implementing Training Programs in Developing Countries - Honorati, Maddalena; McArdle, Thomas P. (World Bank, Washington, DC, 2013)
Training programs mainly address market failures related to lack of skills (technical, cognitive, non-cognitive). This paper conducts a comprehensive review of training programs effectiveness in developing countries. Based on relevant international experiences, the paper highlights key design features associated with program success as well as implementation challenges and discusses their policy implication. Success of training programs is deeply related with the content of the skills provided and how well they serve the local labor demand (demand-driven design) and with the presence of a sound governance structure for training providers and beneficiaries. In particular, the effectiveness of training programs for youth tends to be higher when a 'comprehensive' approach is taken by combining different types of training with complementary support services. The ultimate goal is to inform new program design and improve the performance of current training programs.